Optimalisasi Postur Kerja Administrator Data dengan Pendekatan Metode RULA Studi Kasus Kantor POLRESTA Bandara - Nabila Muthiah Zahra; Rusmalah; Ismi Mashabai; Dirga Elang Permana (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
Data administration activities are generally performed in a static sitting position and require prolonged computer use, which may increase the risk of musculoskeletal disorders (MSDs). This study aims to evaluate the working posture of a data administrator at the POLRESTA Airport Office and propose ergonomic improvements. The Rapid Upper Limb Assessment (RULA) and Nordic Body Map (NBM) methods were employed to assess postural risks and identify musculoskeletal complaints. The results showed a RULA score of 7, indicating a high-risk posture that requires immediate corrective action. NBM findings revealed discomfort in the neck, shoulders, back, and wrists. Proposed improvements include adopting a more upright sitting posture, optimizing monitor viewing distance, using a laptop stand, and providing an ergonomic chair. These recommendations are expected to reduce MSD risks and improve work comfort and productivity.